Reseeding improved productivity but not soil functions in the severely degraded alpine meadows on the Qinghai‐Tibetan Plateau - Liu, Yifan; Meng, Lingchao; Fang, Hui; Dang, Zhiqiang; Zhao, Jingxue; Wu, Gao‐Lin (Restoration ecology, 2025)
Alpine meadows experienced severe degradation and undermined their capacity to support ecological functions such as water supply and carbon storage. It is unclear whether reseeding grasslands over a dozen years for severely degraded alpine meadows could succeed in restoring multiple ecological functions to the levels of original alpine meadow ecosystems. Here, we examined the changes in five ecological functions, including above‐ and below‐ground productivity, soil water holding capacity, soil organic carbon stocks, and soil erosion resistance capacity of alpine meadows before and after degradation, as well as the 14‐year reseeding grasslands. Results showed that severe degradation significantly reduced plant species richness, changed plant community structure, as well as declined ecological functions. For the 14‐year reseeding grasslands, plant species richness and functional group composition could not be restored to the levels of original alpine meadow ecosystems, as well as the soil water holding capacity, soil organic carbon stocks, and soil erosion resistance capacity. Aboveground biomass of sedge species and leguminous species in the reseeding grasslands was still 58.9% and 71.6% lower than those of alpine meadows, respectively. Overall, our results propose that the reseeding grasslands over a dozen years for severely degraded alpine meadows could not succeed in restoring multiple ecological functions to the levels of original alpine meadow ecosystems except for productivity. The results indicated that further restoration and management measures were needed to promote the recovery of multiple ecosystem functions based on the primary goals of sedge species restoration and the formation of mattic epipedon in alpine meadow ecosystems.